Recovery behavior in Fe-32Mn-6.5Si alloy - Jee, K.K.; Lee, J.Y.; Jang, W.Y.; Shin, M.C.; Choi, C.S. (Proceedings of the 1996 International Conference on Displacive Phase Transformations and their Applications in Materials Engineering, 1996)
Variations of recovered strain and temperature with deformation mode (rolling or tension), the amount of pre-strain and microstructure prior to deformation are studied in an Fe-32Mn-6Si alloy. Anomalous recovery behaviors (amnesia and two-step recovery) are found in the rolled specimens. Microstructure, varied by heat treatment after cold rolling, significantly affects shape recovery strain and temperature. A new way of measuring volume fraction of stress-induced ε martensite is proposed, where dilatometry is used.